A comprehensive review on biodiesel purification and upgrading - Hamed Bateni; Alireza Saraeian; Chad Able (Biofuel Research Journal, 2017)
Serious environmental concerns regarding the use of fossil-based fuels have raised awareness regarding the necessity of alternative clean fuels and energy carriers. Biodiesel is considered a clean, biodegradable, and non-toxic diesel substitute produced via the transesterification of triglycerides with an alcohol in the presence of a proper catalyst. After initial separation of the by-product (glycerol), the crude biodiesel needs to be purified to meet the standard specifications prior to marketing. The presence of impurities in the biodiesel not only significantly affects its engine performance but also complicates its handling and storage. Therefore, biodiesel purification is an essential step prior to marketing. Biodiesel purification methods can be classified based on the nature of the process into equilibrium-based, affinity-based, membrane-based, reaction-based, and solid-liquid separation processes. The main adverse properties of biodiesel – namely moisture absorption, corrosiveness, and high viscosity – primarily arise from the presence of oxygen. To address these issues, several upgrading techniques have been proposed, among which catalytic (hydro)deoxygenation using conventional hydrotreating catalysts, supported metallic materials, and most recently transition metals in various forms appear promising. Nevertheless, catalyst deactivation (via coking) and/or inadequacy of product yields necessitate further research. This paper provides a comprehensive overview on the techniques and methods used for biodiesel purification and upgrading.